Unsteady hybrid nanofluid flow over a radially permeable shrinking/stretching surface - Ishak, Anuar; Khan, Umair; Waini, Iskandar; Pop, Ioan (Elsevier B.V., 2021)
The time-dependent stagnation point flow (SPF) and heat transfer of a water-based hybrid nanofluid (Cu − Al2O3/Water) from a radially permeable shrinking or stretching surface is examined. The similarity technique is employed to transform the governing equations of hybrid nanofluid (Cu − Al2O3/Water) into similarity equations. These similarity equations are solved numerically using bvp4c function in MATLAB software. The numerical outcomes are acquired for particular values of the selected parameters. The results notice that dual solutions exist, up to a definite amount of the suction, unsteady strengths, and nanoparticle volume fraction. The critical amount declines due to nanoparticle volume fraction and augments due to suction and unsteady parameters. Also, it is seen that hybrid nanofluid (Cu − Al2O3/Water) augments the rate of heat transfer relative to the regular fluid. The temporal stability analysis is implemented to determine the stability of the dual solutions, and it is found that only one of them is stable and thus physically reliable as time passes.